1998
DOI: 10.1074/jbc.273.43.28019
|View full text |Cite
|
Sign up to set email alerts
|

Coiled-coil Interaction of N-terminal 36 Residues of Cyclase-associated Protein with Adenylyl Cyclase Is Sufficient for Its Function in Saccharomyces cerevisiae Ras Pathway

Abstract: In the budding yeast Saccharomyces cerevisiae, association with the 70-kDa cyclase-associated protein (CAP) is required for proper response of adenylyl cyclase to Ras proteins. We show here that a small segment comprising the N-terminal 36 amino acid residues of CAP is sufficient for association with adenylyl cyclase as well as for its function in the Ras-adenylyl cyclase pathway as assayed by the ability to confer RAS2Val-19 -dependent heat shock sensitivity to yeast cells. The CAPbinding site of adenylyl cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 40 publications
2
43
1
1
Order By: Relevance
“…S1C). This region of yeast Srv2/CAP is predicted to form a coiled coil (Nishida et al, 1998), but this feature may not be conserved in C. elegans CAS-1 (see Discussion). The central region of C. elegans CAS-1 has a proline-rich region (P1) and a WASP-homology 2 (WH2) domain (supplementary material Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S1C). This region of yeast Srv2/CAP is predicted to form a coiled coil (Nishida et al, 1998), but this feature may not be conserved in C. elegans CAS-1 (see Discussion). The central region of C. elegans CAS-1 has a proline-rich region (P1) and a WASP-homology 2 (WH2) domain (supplementary material Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the lack of a second proline-rich region, we noticed a potential difference between CAS-1 and other CAPs in the N-termini. The N-terminal end of yeast Srv2/CAP is predicted to form a coiled coil and implicated in its association with adenylate cyclase (Nishida et al, 1998) or oligomerization (Quintero-Monzon et al, 2009). Analysis by COILS, a prediction tool for coiled coils (Lupas et al, 1991), indicates that the N-terminal region of yeast Srv2/ CAP exhibits high probability of forming a coiled coil, but an equivalent region of C. elegans CAS-1 shows very low probability of forming a coiled coil (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…1A); this region of yeast Srv2/ CAP is sufficient for binding to adenylyl cyclase, an enzyme that produces cAMP (Nishida et al, 1998) and is required for selfoligomerization of Srv2/CAP (Quintero-Monzon et al, 2009). However, this N-terminal region is unstructured in solution (Mavoungou et al, 2004) and coiled-coil formation has not been structurally demonstrated thus far.…”
Section: Domain Organization Of Capmentioning
confidence: 99%
“…Additional signal transduction components appear to contribute to glucose signaling by contacting adenylate cyclase (Cyr1); such Cyr1 protein-protein interactions identified thus far include those with (i) an N-terminal SH3 domain in the RasGEF Cdc25 (237), (ii) the farnesylated Ras2 C terminus (73,74,184,199,338,355), (iii) the C terminus of the putative cochaperonin Sgt1 (95), (iv) the N terminus of the ancillary factor Srv2 (CAP) via coiled-coil formation (267), and (v) the RasGAP Ira1, which mediates peripheral association of adenylate cyclase with the yeast plasma membrane (241).…”
Section: Early Steps In Signal Transductionmentioning
confidence: 99%